Educational criteria regarding child’s films and animations from the perspective of Islamic theory of action - Narges Sadat Sajjadieh; Sadigheh Soltanynejad (تربیت اسلامی, 2023)
While there are many pieces of research about the technical dimensions of animation, its educational dimensions are not studied. The main research question of this paper is: what educational−psychological criteria should be considered in the child's media (animation) based on Islamic theory of action? The method approach used in this research is progressive inference, in which, regarding the educational goals and principles of the Islamic theory of action, the educational−psychological criteria of the film and the child's animation are implicitly extracted. We can classify the criteria into five categories: Criteria for physical and mental health, Criteria for familiarizing children with moral/religious values, Criteria for strengthening children's thinking, Criteria for enforcement of the dispositions of the choosing and responsibility in children, and Criteria for dynamist rational identities. Some of these criteria are as follows: avoiding the institutionalization of negative emotions in the audio−visual and narrative aspects of animation; avoiding negative themes and issues such as violence and sexual relations in narratives and visual effects, step−by−step and delayed encountering with dolorous realities in the narrative−visual structure of animation, explanatory attention to moral−religious values, avoidance of information saturation, attention to clarity and value embodiment in animation, designing real−life values in the narration, following the narrative structure of the animation from the causal and linear structures of narration, highlighting the choosing and decision making situations in animation, considering the process of the life in animation, and attempting to diversify the identities.